Puerariae lobatae radix protects against UVB-induced skin aging via antagonism of REV-ERBα in mice - Ma, Luyao; Huang, Meiping; Sun, Guanghui; Lin, Yanke; Lu, Danyi; Wu, Baojian (Frontiers in Pharmacology, 2022)
Puerariae lobatae radix (PLR) is a wildly used herbal medicine. Here we aimed to assess the PLR efficacy against UVB (ultraviolet-B)-induced skin aging and to determine the mechanisms thereof. We found a significant protective effect of PLR (topical application) on UVB-induced skin aging in mice, as evidenced by reduced skin wrinkles, epidermal thickness, and MDA (malondialdehyde) content as well as increased levels of HYP (hydroxyproline) and SOD (superoxide dismutase) in the skin. In the meantime, Mmp-1, p21 and p53 levels were decreased in the skin of PLR-treated mice. Anti-aging effects of PLR were also confirmed in L929 cells. Furthermore, PLR up-regulated skin expression of BMAL1, which is a known regulator of aging by promoting Nrf2 and antioxidant enzymes. Consistently, Nrf2 and several genes (i.e., Prdx6, Sod1, and Sod2) encoding antioxidant enzymes in the skin were increased in PLR-treated mice. Moreover, based on Gal4 chimeric assay, Bmal1 reporter gene and expression assays, we identified PLR as an antagonist of REV-ERBα that can increase Bmal1 expression. Intriguingly, loss of Rev-erbα protected mice against UVB-induced skin aging and abrogated the protective effect of PLR. In conclusion, PLR acts as an antagonist of REV-ERBα and promotes the expression of BMAL1 to protect against skin aging in mice.